PENGARUH PELAKSANAAN PURSED LIPS BREATHING TERHADAP FREKUENSI PERNAFASAN PASIEN PENYAKIT PARU OBSTRUKSI KRONIK (PPOK) DI RSUD DR. PIRNGADI KOTA MEDAN TAHUN 2022 - ALMINA ROSPITARIA TARIGAN (LP2MTBM MAKARIOZ, 2022)
COPD patients have an increased respiratory rate with prolonged expiration as compensation for shortness of breath. Pursed lip breathing is an exercise that aims to regulate the frequency and pattern of breathing so as to reduce air trapping, improve ventilation of the alveoli to improve gas exchange without increasing the work of breathing, regulate and coordinate respiratory rate so that breathing is more effective and reduces shortness of breath. This study aims to determine the effect of pursed lips breathing on the respiratory frequency of patients with chronic obstructive pulmonary disease (COPD) in RSUD DR. Pirngadi Medan City, with the type of experimental research that is time series design. The population in this study were all COPD patients who were treated at RSUD DR. Pirngadi Medan City in March and the average number of patients every month is 22 patients. The sampling technique used is total sampling. Data collection is done by using observation. Data analysis was performed bivariately with paired sample t-test at 95% confidence level, =5%. The results showed that the respiratory frequency before pursed lips breathing was performed, namely the majority of abnormal breathing frequencies were 14 people (63.6%) and the respiratory frequency after pursed lips breathing was the majority of normal breathing frequencies were 15 people (68.2%). There is an effect of the implementation of pursed lips breathing on the respiratory frequency of patients with chronic obstructive pulmonary disease (COPD) in RSUD DR. Pirngadi Medan City. Based on the results of statistical tests using the dependent test sample t-test/paired t test, it shows that the pValue is 0.002. For nurses to be able to improve health, especially in the process of healing COPD and be able to apply pursed lips breathing settings independently so that they can improve respiratory frequency.